Analisis Penerapan Perencanaan Pajak PPh Pasal 21 Wajib Orang Pribadi di PT Sukses Anugrah Sejahtera - Anggi Pratiwi Sitorus; Owen De Pinto Simanjuntak (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
PT. Anugrah Prosperous SuccessWhere this limited liability company is one of the businesses providing vehicle maintenance services.the reason why PT was chosen by the researcher.Because of the possibility of excessively high taxes, Anugrah Sejahtera's success, it is still possible to plan for these businesses' taxes to reduce their burden.This is consistent with the information regarding the Article PPH Income Tax's burden and benefit.This study aims to learn about and examine how PT applies income tax planning article 21 to individual taxpayers.Anugrah Prosperous SuccessResearch Strategies Gathering information as per research needs, assessing the information as worker finance for allowances and computing PPh 21 at PT.Achievement Anugrah Sejahtera, checking organization representative pay rates then, at that point, making charge anticipating compensations by expanding prohibited pay, directing meetings, choosing bookkeeping techniques that are as per charge guidelines lastly reaching determinations.This study's findings indicate that PT.According to the applicable Tax Law, Sukses Anugrah Sejahtera (SAS) has not calculated and deducted income tax from its employees.The conclusion then drawn is that PT employees.In the tax calculation section, Success Anugrah Sejahtera (SAS) has not fully mastered the applicable PPh21 tax regulations, such as determining job costs, using layers of progressive rates, and accepting sanctions for those without an NPWP.